Obstetric outcome of floating head in primigravida at term - Pahwa, Sangeeta; Kaur, Arshdeep; Nagpal, Madhu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Engagement of head is the most important event in labor which decides obstetric outcome. Floating head in primigravida at term is considered an important obstetric risk factor. Cephalopelvic disproportion, occipito-posterior position and deflexed head should be suspected in most cases of floating head. Present study was conducted to determine the outcome of labor in primigravida with floating head at term. The primary objectives of the study was to analyse the progress of labor, need of medical and surgical interventions and fetomaternal outcome. The secondary objective was to find out the rate of caesarean section for floating head in all situations whether elective or emergency in labor. Methods: This study was conducted in department of Obstetrics and Gynaecology SGRDIMS and R, Sri Amritsar on 100 primigravida subjects with floating head at term admitted through OPD admissions for induction of labor /spontaneous labor or referred from outside directly in early labor. Results: In present study the mean age was 24.95±3.01 years. The youngest case was 19 years old and eldest being 32 yrs old. The mean height was 151±3.41. At the time of admission 21% of cases had floating head, 55% cases were at -3 station, 17% of cases had -2 station, with only 7% of cases had -1 station. 56% of women delivered by caesarean section, 8% by forceps assisted vaginal delivery and 36% by normal vaginal delivery. The mean duration of labor was more in free floating and -3 stations in comparison to -2, or -1 stations. The need for augmentation was more in higher head stations. Mean birth weight was 2.84±0.31, it was more in higher fetal stations in comparison to lower fetal stations. No significant maternal and fetal morbidity was seen. There was no significant difference in the Mean APGAR score of higher head stations in comparison to lower fetal stations. Conclusions: Primigravida with floating head at term and during labor should be managed cautiously. By proper monitoring and maintenance of partogram most of these cases deliver vaginally and without any maternal and fetal morbidity. The attitude of watchful expectancy and timely intervention will be used in all cases, especially in those appearing to be taking a protracted course.